Arabic Mamluki Monetary Inscription: Historical Linear Linguistic Analytical Study - Zaal Al-Khamaiseh, Ali (Opción, 2019)
The subject of the study is an inscription of a golden Mamluki inscription written in the Thuluth script, dating back to the reign of Abi-Nasr in Presbai, the Circassian Sultan and the King of Egypt (766-841 H = 1365-1438 A.D). His name was inscripted on the second face of the coin piece.The dinar was decorated with Helal and a palm tree as Islamic symbols, yet the process of in- scription was not perfect; as there was no harmony between the sizes of words and the letters. The punctuation of the letters was neglected, the dropping of the truncheons and some words, so as not to exceed the permissible weight of the dinar. It weighed between three grams and three grams and a half grams during the reign of Abi-Nasr Presbai.